Constructing And Designing A Reluctance And Initiative Scale And Its Relationship To Physical Education Female Teachers Participating In Sports Competitions In Maysan Governorate - Al-Krizi, Maitham Mutair Hamidi (Universitas Tanjungpura, 2025)
Reluctance and initiative are important psychological dimensions that influence teachers